Analisis Kebutuhan Sertifikasi Pelatihan Karyawan Untuk Pengembangan Karyawan Pada PT PLN Nusantara Services - Fitri A'isya; Ni Made Ida Pratiwi; Rachmat Risanto Tiesa (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2024)
This research aims to analyze the certification training needs of employees for their development at PT PLN Nusantara Power Services. In the context of increasing industry competition and rapid technological advancements, the need for relevant certifications and training has become crucial to enhance employee competence and competitiveness. The research employs a qualitative approach, collecting data through interviews and observations. The findings indicate several key areas where training certification is highly needed, including technical fields, occupational safety, and project management. Furthermore, the results reveal that structured and continuous certification programs can boost employee motivation and performance, supporting the achievement of the company's strategic goals. Recommendations from this research include the development of training curricula that align with industry needs, increased collaboration with external certification institutions, and the development of a continuous evaluation system to ensure the effectiveness of the certification programs. Thus, the implementation of these training certification programs is expected to contribute positively to the human resource development at PT PLN Nusantara Power Services.